Out-of- hospital mortality in the municipality of Cienfuegos, 2016 - Orlando Morera Álvarez; Daylin Madruga Jiménez; Liliana Caridad Romero Castro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: Mortality data indicate the number of deaths by place, time interval and cause. The evolution of this evidence is the combination of the problems characteristic of the populations living conditions and the conflicts of developing countries. In addition, mortality patterns are changing the some specific groups epidemiological profile. Objective: to describe the behavior of out-of-hospital mortality in the Cienfuegos municipality. Methods: descriptive, cross-sectional study, with the total number of deceased patients over 15 years of age, outside hospital institutions in the Cienfuegos municipality, in 2016 (N =1821). It was analyzed: place of occurrence, age, sex and cause of death; the latter, according to the International Classification of Diseases in its 10th edition. Results: 86.4 % of deaths occurred at home, with a male predominance (50.4 %), and of people 65 years of age and older. Malignant tumors were the leading cause of death (rate of 79.1 x 10,000 inhabitants), followed by heart disease. Conclusion: the results obtained in the present study regarding the variables studied are similar to those of other research, both from national and foreign authors.